2020
DOI: 10.1111/odi.13715
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion in individuals with osteogenesis imperfecta: A systematic review and meta‐analysis

Abstract: Objective: To evaluate whether individuals with osteogenesis imperfecta (OI) are more affected by malocclusion than individuals without OI. Materials and Methods: Searches in PubMed, Ovid, Web of Science, Scopus, Lilacs and gray literature were performed. Data extraction was conducted by two researchers. Risk of bias assessment employing the Newcastle-Ottawa Scale and meta-analysis were conducted. Results were provided with mean difference (MD), odds ratio (OR) and 95% confidence interval (CI). Strength of evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
(170 reference statements)
0
8
0
Order By: Relevance
“…Existing reviews of OI literature do not provide a systematic overview of the scope of published records, but rather follow a narrative design [ 61 – 63 ], or aim to answer specific research questions [ 9 , 11 , 18 21 , 64 72 ]. Therefore, the aim of this review was to determine the breadth of literature available and provide a snapshot of the evidence it covers.…”
Section: Discussionmentioning
confidence: 99%
“…Existing reviews of OI literature do not provide a systematic overview of the scope of published records, but rather follow a narrative design [ 61 – 63 ], or aim to answer specific research questions [ 9 , 11 , 18 21 , 64 72 ]. Therefore, the aim of this review was to determine the breadth of literature available and provide a snapshot of the evidence it covers.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the prevalence of malocclusion is high among individuals diagnosed with OI and the frequency and severity vary significantly among the different types of the disease (Hidalgo-Perea & Green, 2021;Rizkallah et al, 2013;Retrouvey et al, 2019;Prado et al, 2022). Besides the systemic clinical consequences caused by OI, the high prevalence of malocclusion can affect the functioning of the stomatognathic system in this portion of the population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that class III malocclusion with anterior crossbite is the more frequently found in individuals with OI compared to individuals without this disease (Prado et al, 2022). The growth of all craniofacial bones is affected by OI due to defects in intramembranous or endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abnormal bone growth, posture, head size might be contributing factors to the development of malocclusions, which may become more serious with time [20]. Malocclusions can impair everyday activities such as chewing and speaking and consequently have negative impact on quality of life [12,24], which was one of the main concerns of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusions can impair daily activities, such as chewing and speaking, which has negative impact on quality of life and serious psychological and social implications [12]. Also, affected teeth might have crowns with a bulbous structure, constriction in the cementoenamel junction, irregular root morphology, enlarged pulp chamber as well as pulp stones and obliterations [13,14].…”
Section: Introductionmentioning
confidence: 99%